The OsMPK15 Negatively Regulates Magnaporthe oryza and Xoo Disease Resistance via SA and JA Signaling Pathway in Rice - Hong, Yongbo; Liu, Qunen; Cao, Yongrun; Zhang, Yue; Chen, Daibo; Lou, Xiangyang; Cheng, Shihua; Cao, Liyong (Frontiers in Plant Science, 2019)
Mitogen-activated protein kinase (MAPK) cascades play central roles in response to biotic and abiotic stresses. However, the mechanisms by which various MAPK members regulate the plant immune response in rice remain elusive. In this article, to characterize the mechanisms, the knock-out and overexpression mutants of OsMPK15 were constructed and the disease resistance was investigated under the various fungal and bacterial inoculations. The knock-out mutant of OsMPK15 resulted in the constitutive expression of pathogenesis-related (PR) genes, increased accumulation of reactive oxygen species (ROS) triggered by the pathogen-associated molecular pattern (PAMP) elicitor chitin, and significantly enhanced the disease resistance to different races of M. oryzae and Xanthomonas oryzae pv. oryzae (Xoo), which cause the rice blast and bacterial blight diseases, respectively. On contrary, the expression of PR genes and ROS were down-regulated in the OsMPK15-overexpressing (OsMPK15-OE) lines. Meanwhile, phytohormones such as salicylic acid (SA) and jasmonic acid (JA) were accumulated in the mpk15 mutant lines but decreased in the OsMPK15-OE lines. The expression of SA- and JA-pathway associated genes were significantly upregulated in the mpk15 mutant, whereas it was down regulated in the OsMPK15-OE lines. We conclude that OsMPK15 may negatively regulate the disease resistance through modulating SA- and JA-mediated signaling pathway.